Pronomes pessoais do caso reto em livros didáticos de Língua Portuguesa: um estudo à luz do sociofuncionalismo - Moreira, Cileya de Fátima Neves (2024)
This research aims to investigate the treatment given to personal pronouns in Portuguese Language Textbooks for the Final Years of Elementary School, approved by the National Textbook Program (PNLD) (four-year period 2024-2027), from a sociofunctionalist perspective, which is a proposal from Variationist Sociolinguistics with North American Functionalism. For this theory, the language and its varieties are analyzed in their use. Our research is based on Labov (2008[1978]), Tarallo (2007), Castilho (2012), Neves (1997, 1999), Givón (1995, 2001), Tavares (2003), Görsky and Tavares (2013). As for the characterization, it is classified as descriptive, propositional, documentary, with a qualitative approach and bibliographic method. The research corpus consists of eleven collections of textbooks, each containing four volumes, amounting 44 volumes, of which 13 were analyzed, as they include the phenomenon under investigation. In the methodology, the research questions that approach linguistic and extralinguistic variables in language teaching are analyzed and include activities involving linguistic variation in the teaching of personal pronouns, with emphasis on their use in social interactions. The analysis was then segmented into three categories, according to a greater, lesser and/or absent appreciation of the phenomenon: affirmative, partial or negative. The results show that most of the textbooks analyzed address, directly and/or indirectly, the teaching of personal pronouns. In addition, we proposed, in our dissertation, a pedagogical notebook, whose activities consider the functioning, reflection and use of personal pronouns, considering linguistic unity in diversity, the effects of meaning created by the choices of one form or another and the adequacy of this usage to the communicative situation.